Buckling failure of rectangular oil tank with corrugated wall - Chng, Benjamin Chi Tze (Nanyang Technological University, 2023)
Corrugated walls are used due to the advantages it exhibits such as low mass, easier maintenance, and fewer issues with corrosion. Moreover, corrugated bulkhead improves the lateral flexibility and vertical rigidity making them a common choice for oil transportation. However, corrugated bulkhead is subjected to various type of damages, but the most common damage is buckling. Buckling is a structural failure that happens suddenly and incur huge deformation in the buckle area. This project aims to investigated how varying corrugation depth and thickness of the corrugated wall fails and how it will affect the strength and buckling mode of the wall. The corrugated wall is modelled using SolidWorks, then imported into a Finite Element Analysis (FEA) software called ANSYS to be analysed. Only 1 corrugated wall will be analysed, and the boundary conditions used for this analysis are assumed to be fixed support for the 2 vertical and 2 horizontal edges. Analysis will be conducted to predict the critical buckling load and the buckling location for 16 mm thick wall with varying corrugation depth. Thickness of 17 mm, 18 mm, 19 mm, and 20 mm with varying corrugation depth were further analysed to determine the buckling load and location for this project. Nonlinear buckling analysis is carried out which includes the nonlinearity of the material and geometry. Loading for this project includes a constant hydrostatic pressure and a surcharge pressure up to 4 bar applied across the entire wall surface. Results from the nonlinear buckling analysis shows the buckling load and location of the 16 mm thick wall with varying depth. The result obtained differ from analysis done by Kek (2017) and Riyad (2018). However, results do show that with increase depth and increase thickness the strength of the wall increases. It also showed the buckling location along the flange web was located near to the edge of the flange breadth where it is high stress concentration region.